105k views
16 votes
Enter the value of n so that the expression (5y - 2.3) + (-2y -4.3)
is equivalent to (3y-n).

User Playmaker
by
5.0k points

1 Answer

8 votes

Answer:

Explanation:

(5y - 2.3) + (-2y - 4.3) = 3y - n Remove the brackets

5y - 2.3 - 2y - 4.3 = 3y - n Combine like terms

3y - 6.6 = 3y - n Subtract 3y from both sidess

- 6.6 = - n Divide by - 1

6.6 = n

User Jacqueline Nolis
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.